Crystal Structure of the Gold Nanoparticle [N(C8H17)4][Au25(SCH2CH2Ph)18] - Heaven, Michael W; Dass, Amala; White, Peter S; Holt, Kennedy M; Murray, Royce W (Journal of the American Chemical Society, 2008)
We report the crystal structure of the thiolate gold nanoparticle [TOA+][Au25(SCH2CH2Ph)18 -], where TOA+ = N(C8H17)4 +. The crystal structure reveals three types of gold atoms:  (a) one central gold atom whose coordination number is 12 (12 bonds to gold atoms); (b) 12 gold atoms that form the vertices of an icosahedron around the central atom, whose coordination number is 6 (five bonds to gold atoms and one to a sulfur atom), and (c) 12 gold atoms that are stellated on 12 of the 20 faces of the Au13 icosahedron. The arrangement of the latter gold atoms may be influenced by aurophilic bonding. Together they form six orthogonal semirings, or staples, of −Au2(SCH2CH2Ph)3− in an octahedral arrangement around the Au13 core.